KUALITAS LAPORAN KEUANGAN SEBAGAI DAMPAK DARI KUALITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMITMEN ORGANISASI TERHADAP PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN (Studi pada Pemerintah Daerah Kabupaten Tangerang) - Triana Zuhrotun Aulia; Anita Ardiyanti (Universitas Muhammadiyah Tangerang, 2018)
The purpose of the study is to analyze how much influence the quality ofhuman resources, utilization of information technology and organizationalcommitment to government accounting standards and its impact on thequality of financial statements at the Regional Government of TangerangRegency. The sample of research is 50 employees at the RegionalGovernment of Tangerang Regency who work in accounting/finance. Thesampling technique uses convenience sampling. Data collection usingquestionnaire. The method used in this research is the method ofverification. To determine the effect of human resource quality, theapplication of information technology and organizational commitment tothe application of government accounting standards and the impact on thequality of financial statements. The test statistic used is designing thestructural model, designing a measurement model, construct the pathdiagram, test the model fit. Suitability test structural models and hypothesesusing software SmartPLS 3.0. The results showed that the variable qualityof human resources and organizational commitment have a significanteffect on the application of government accounting standards. While theutilization of information technology has no significant effect on theapplication of government accounting standards. And the application ofgovernment accounting standards have a significant effect on the quality offinancial statements.